Strategy for the Development of Sharia Financial Institutions in the Authority Perspective of Indonesia Financial Services - Chandra Satria; Mohamad Faizal; Choirunnisak Choirunnisak (Sekolah Tinggi Ekonomi dan Bisnis Islam Lampung, 2021)
This research provides an overview by the Republic of Indonesia Financial Services Authority and other research on the development and management strategies of Indonesian Islamic financial institutions, which are the largest Muslim population in the world and have the largest economy in Southeast Asia. The growth of Indonesian sharia financial institutions is quite significant plus high economic growth at the same time. This attracts researchers to explore further whether the Islamic banking sector is currently experiencing growth and growth consistently to contribute empirically to Indonesia's economic growth in the future. Indonesia's Financial Services Authority (OJK) provides an overview and prospects for the growth of several sectors such as national sharia financial industry assets increased by 27% (excluding Sharia shares) higher than conventional financial industry in 2017. The development of Islamic financial products is quite good and varied. It is including an increase in its own Islamic financial infrastructure activities. Recorded data that the overall market share of Islamic finance is still below 5% such as sukuk and corporate bonds circulating 3.99% of the value of the bonds and bonds represent the amount, the net asset value of Syariah mutual funds is 4.4% of the total net asset value of the mutual fund and Sharia insurance amounted to 3.44%. Although there are some Sharia products above 5% such as Islamic banking assets, 5.33% of all banking assets, state sukuk which accounted for 14.82 percent of the total outstanding state securities, Islamic finance institutions amounted to 7.24% of total financing, special Islamic financial services institutions amounting to 9.93% and Sharia microfinance institutions amounting to 22.26% at the end of 2016. Seeing these figures above the Financial Services Authority of the Republic of Indonesia as the regulator in driving financial institutions within the country provides hope and strategic programs that can be optimized to accelerate the growth of Islamic finance in Indonesia, namely by the existence of 1. Enhancing Islamic financial products. 2. Enhancing Sharia services with the use of the latest information technology; 3. Optimizing coordination with stakeholders regarding the development of the Islamic financial industry.